Threshold and mediating effects of new urbanization on residential building carbon emissions: evidence from Chinese pilot cities - Wang, Yongkun; Tong, Zhuo; Zhang, Yunhui (Frontiers in Public Health, 2025)
IntroductionIn the context of China’s new urbanization strategy and its “dual-carbon” goals, understanding the impact of urban transformation on carbon emissions in the residential sector is crucial. This study explores the influence mechanism of new urbanization on carbon emissions from residential buildings using panel data from 58 pilot cities between 2012 and 2021.MethodsA comprehensive analytical framework incorporating fixed-effects, mediation, and threshold models is employed to examine the direct, mediating, and nonlinear effects of new urbanization.ResultsThe empirical findings indicate that: (1) new urbanization has a significant positive impact on residential building carbon emissions; (2) environmental regulation and scientific and technological innovation (STI) serve as mediators, each exhibiting emission-reducing effects within this relationship; (3) both environmental regulation and STI demonstrate double-threshold effects, with the regulatory impact diminishing at higher intensities, while the mediating effect of STI follows a nonlinear U-shaped trend; and (4) the mediating roles of environmental regulation and STI are subject to substantial regional and urban-size heterogeneity, being more effective in eastern regions and megacities.DiscussionThese results offer new empirical insights into the carbon implications of urban development and provide policy guidance for differentiated, region-specific, and innovation-driven carbon reduction strategies in the residential sector.